Measures of Nursing Environment Multidimensionality and Patient Centricity Using Importance-Performance Map Analysis - Andy Andy; Salsabilla Maula Zalfa El-Hamzah; Ferdi Antonio (Nurse Media Journal of Nursing, 2022)
Background: The nursing environment has become a consideration for an organization in improving service quality, especially in the implementation of patient-centred care. The various dimensions make it necessary to know which sectors need to be prioritized. However, there is still limited research that is more specific in linking the dimensions to become more operational.  Purpose: This study aimed to analyze the relationship between nursing environment dimensions and patient centricity through the Importance-Performance Map Analysis (IPMA).Methods: A quantitative survey with a cross-sectional approach was conducted in June 2022 to test the conceptual framework on the population obtained from non-managerial inpatient nurses who worked for above two years in a general hospital in East Java, Indonesia. The constructs were measured using a set of indicators in The Practice Environment Scale of the Nursing Work Index (PES-NWI) and Patient Centricity. During the data collection, a total sampling technique was performed, resulting in 89 respondents being acquired. The data were analyzed through partial least squared structural equation modelling (PLS-SEM).Results:  At the construct level, the mean total effect and performance were 0.192 and 56.302, respectively. From the IPMA chart, it was found that the construct in the right lower quadrant with the largest total effect value but not having adequate performance was nursing manager ability (total effect: 0.294, performance: 34.563), making it a construct with the highest importance and requiring priority for improvement among all dimensions.Conclusion: The nursing environment dimensions have to get attention to achieve patient centricity in inpatient ward nurses, where nursing manager ability is the dimension that has the most vulnerable performance. Leadership development is needed for the head nurse of the inpatient unit to strengthen the ability to lead and change the culture in nurturing subordinates so that kinship between nursing professionals can be established.